Overcoming among‐lineage rate heterogeneity to infer the divergence times and biogeography of the clubmoss family Lycopodiaceae. (7th June 2018) - Testo, Weston; Field, Ashley; Barrington, David
Abstract: Aim: To infer divergence times and historical biogeography of the cosmopolitan lycophyte family Lycopodiaceae. Location: Worldwide. Methods: We generated time‐calibrated phylogenies of the Lycopodiaceae based on six regions of chloroplast DNA using a node‐dating approach implemented inbeast with eight fossil calibrations. To investigate effects of among‐lineage substitution rate heterogeneity on divergence time estimation, we compared the performance of two relaxed clock models: an uncorrelated lognormal clock model and a random local clock (RLC) model. The historical biogeography of the family was inferred using two Bayesian models implemented in BioGeoBEARS. Results: Divergence time estimates for major groups of the Lycopodiaceae obtained using the two substitution clock models differed substantially, and the RLC model was a better fit. The Lycopodiaceae crown group age is estimated to be late Devonian, and most deep divergence events date to the Carboniferous, with most extant species diversity accumulating during the Cenozoic. The timing of divergences of major clades in the Lycopodiaceae corresponds to the breakup of the Pangaean and Gondwanan supercontinents. Long‐distance dispersal events are relatively common, but generally do not appear to be followed by subsequent radiations. Main conclusions: Accounting for among‐lineage substitution rate heterogeneity improves divergence time estimates for the Lycopodiaceae. The family has a deep evolutionary history, and continent‐scale vicariance events in the Mesozoic appear to have been associated with major cladogenesis events, with long‐distance dispersal playing a relatively minor role.